Performance Rating for Small and Medium Size Furniture Manufacturers Under Integrated Marketing Scheme in Peninsular Malaysia - Bawon, Paiman (1999)
The furniture industry in Malaysia has shown rapid expansion. It has been identified as a priority industry for development under the Second Industrial Master Plan (IMP) for the period of 1998 to 2005. Exports value for 1997 amounted to RM3.8 billion, but now the firm footage this industry has in the international market may be lost if the quality of furniture products are not stringently regulated. Performance management in this case is the key to success and therefore it must function efficiently especially at the administrative level and the production process. The objectives of this study were to identify the level of performance required, to study the current level of performance practiced, to highlight areas for improvemnet and to establish an acceptable performance standards that can be used as a guideline for Bumiputra manufacturers under the integrated marketing scheme anchored by Guthrie Furniture Sdn. Bhd. The results of the study showed that most of the manufacturers were in the D grade (lack of performance in a number of areas) and the E grade (performance is generally unacceptable) in which corrective actions are necessary for improvement. Production and management aspects were interrelated and contributed to changes in the level of quality finishing of furniture. In general, the major factors influencing performance were machine, raw material, maintenance, training, administrative and labour. Three specific factors affecting performance as shown through this study were the level of automation, frequency of training, and frequency of management meeting. Other factors were good housekeeping of the work area, raw material recovery, average production capacity, local or international market, maximum production capacity, maintenance schedule, waste disposal, labour cost, working capital, skills and knowledge in operations, labour turnover, paid-up capital and overall skills and knowledge of workers. It is hoped that the information obtained from this study will be able to assist the Guthrie Furniture Sdn. Bhd. to plan and provide better assistance and guidance to the manufacturers to improve performance in management and production. The influences defined as critical indicators in the performance analysis should be included in the performance rating standard.